2010
DOI: 10.1186/1471-2474-11-113
|View full text |Cite
|
Sign up to set email alerts
|

A within-subjects trial to test the equivalence of online and paper outcome measures: the Roland Morris Disability Questionnaire

Abstract: BackgroundAugmenting validated paper versions of existing outcome measures with an equivalent online version may offer substantial research advantages (cost, rapidity and reliability). However, equivalence of online and paper questionnaires cannot be assumed, nor can acceptability to respondents. The aim was to test whether online and written versions of the Roland Morris Disability Questionnaire (RMDQ), a standard measure of functional disability in back pain, are equivalent at both group and individual level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 18 publications
1
27
0
2
Order By: Relevance
“…38 In a recent meta-analysis concerning PROMs equivalence between computer and paper versions, the average correlation of 278 PROMs was excellent 21 similar to responses to a comparison across 16 health-related measures. 42 None of the current foot and ankle or more generic PROMS had been previously evaluated, 21 but the demonstrated limits of agreement 4 identi ed no systematic bias and compared well to previously reported questionnaire properties. 20 For example, our FAOS results (LoA = 9.13) compared favourably with published minimally important subscale differences ranging from 5.8 to 11.1, 15 giving con dence about online use.…”
Section: İnterpretation Of Outcomes Validitysupporting
confidence: 54%
“…38 In a recent meta-analysis concerning PROMs equivalence between computer and paper versions, the average correlation of 278 PROMs was excellent 21 similar to responses to a comparison across 16 health-related measures. 42 None of the current foot and ankle or more generic PROMS had been previously evaluated, 21 but the demonstrated limits of agreement 4 identi ed no systematic bias and compared well to previously reported questionnaire properties. 20 For example, our FAOS results (LoA = 9.13) compared favourably with published minimally important subscale differences ranging from 5.8 to 11.1, 15 giving con dence about online use.…”
Section: İnterpretation Of Outcomes Validitysupporting
confidence: 54%
“…Third, although a consistent data collection format is generally recommended [55], we used both Internet-based and paper surveys. However, prior research has demonstrated similar psychometric properties between Internet and paper-and-pencil questionnaires [55] and specifically equivalence for our primary outcome [56]. We also believe that using both modes helped to ensure a high follow-up rate.…”
Section: Discussionmentioning
confidence: 58%
“…A wide variety of studies have previously shown good equivalence between electronic and paper questionnaires [2,8,9,10,11,12,13,14,15,16,17], but it is still generally recommended to evaluate measurement properties of the electronic version separately, rather than expecting validations of the paper version to a priori be extrapolated to the electronic version [1,3]. Thus, the aim of the present study was to assess the equivalence between the paper version and the electronic version of the ThyPRO questionnaire [1].…”
Section: Introductionmentioning
confidence: 99%